{Demonstrate the Double Negative Behavior of Metamaterial Using the Effective Medium Theory - Tung, Nguyen Thanh; Hoai, Pham Van; Binh, Nguyen Trung; Hong, Le Van; Lam, Vu Dinh; Lee, Y. P. (Communications in Physics, 2012)
We fabricated the electric and magnetic metamaterial, and measured their transmission spectra. The electromagnetic response of the combined structure, which consists of cut-wire pair and continuous wire, are experimentally and numerically studied in the microwave frequency regime. The simulations are performed in a qualitative agreement with experiment utilizing the transfer-matrix method. The double negative behavior of combined structure is observed and demonstrated using the effective medium theory.